Latent Factors of Sustainable Tourism Practices and Green Hospitality Measures in Gilgit Baltistan, North Pakistan - Muhammad Qasim; Atta-ur-Rahman; Takaaki Nihei; Zaheer Ahmed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
The tourism activities and hospitality services are part and parcel to each other; therefore, adaptation of green management within hospitality services is inevitable for development of tourism in sustainable way. The current study therefore determines the factors responsible for development of tourism in sustainable way and green management within hospitality entities throughout Gilgit Baltistan (GB) region. Quantitative data through a structured set of questionnaires is acquired from the registered hospitality units of the study area including hotels and guest houses. Yamane’s formula is used to specify the sample size from the targeted population. Following the result of applied formula, 177 hospitality managers out of 499 total registered hospitality units are approached from all the three divisions of Gilgit Baltistan. To determine the latent factors, factor analysis is applied on the data through statistical software. To ensure the appropriateness of the statistical analysis, Kaiser-Mayer-Olkin (KMO) and Bartlett’s test is applied initially. KMO sampling adequacy of 0.626 and Bartlett’s test of sphericity with most significant value of (p < 0.001) endorsed the appropriateness of the proposed analysis. Rotated Components Matrix through Kaiser Normalization concluded seven latent factors with different components of variances including six factors related to hospitality management services. Hence, green management in hospitality is necessary for sustainability in tourism.